Fascism, Populism and the Myth of the American Revolution in 20th Century US Literature - Paladin, Nicola (Oltreoceano - Rivista sulle migrazioni, 2021)
This essay sets out to observe the significance of the American Revolution as a literary trope and a rhetorical device in shaping US political imagination. Particularly, the Revolution served both utopian and dystopian rationales, including radical experiences such as fascism. I will examine this relevance in Nathanael West’s A Cool Million (1934) and Sinclair Lewis’s It Can’t Happen Here (1935). Fascismo, populismo e mito della Rivoluzione Americana nella letteratura statunitense del XX secolo Il saggio intende analizzare il ruolo della Rivoluzione americana come tropo letterario e strategia retorica nella formazione dell’immaginario politico statunitense. In particolare, la Rivoluzione ha alimentato logiche sia utopiche sia distopiche, sfociando in derive radicali come il fascismo. Saranno qui esaminati A Cool Million (1934) di N. West e It Can’t Happen Here (1935) di S. Lewis.